PENGUATAN PEMBELAJARAN KONTEKSTUAL MELALUI KUNJUNGAN INDUSTRI: STUDI KUALITATIF PADA MAHASISWA PROGRAM STUDI S1 MANAJEMEN STIE PEMUDA DI PT. ATLANTIC BIRURAYA - Nuryadi; Abu Darim; Dewi Anjani; Ayunda Bella O; Salva Nur H; Umar Luthfi; Rifaldo Jefri S (Jurnal Multidisipliner Bharasumba, 2026)
This research aims to understand the strengthening of contextual learning through industrial visits for undergraduate Manag ement students at STIE Pemuda, specifically at PT Atlantic Biruraya. The study employs a qualitative method with a case study approach. Data were collected through interviews, observations, and documentat ion. The findings indicate that industrial visits significantly enhance contextual learning by providing students with direct, real-world exper iences and expanding their understanding of how human resource man agement concepts are applied in actual business practices. Through these activities, students are able to bridge the gap between theoretical knowledge gained in the classroom and its practical implementation in the workplace, industrial visits contribute to improving students’ critic al thinking, adaptability, and professional awareness. For business ma nagement students, such experiential learning opportunities are essent ial in preparing them for future careers, as they foster relevant compet encies, practical insights, & a deeper understanding of organizational dynamics in a competitive business environment.